KUSISDARI USM SEEKS CROSS-BORDER EXPERIENCE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 29 June 2015 – The Kumpulan Siswasiswi Darul Ridzuan (KUSISDARI) of Universiti Sains Malaysia (USM) crossed international borders to visit Australia in search of experience and global networking. With 'Exchange Knowledge Beyond Boundaries' as the theme of the visit, the 15member delegation comprising student leaders of KUSISDARI carried out various activities during their recent study trip to Murdoch University in Perth, Australia.